Computation of Nonequilibrium Hypersonic Flow over Concave Corners (Journal of Computational Mathematics, 2021)
This paper is devoted to computation of hypersonic flow of air with chemical reactions over concave corners. A technique combining smooth transformation of domain and implicit difference methods is used to overcome numerical difficulties associated with the lack of resolution behind the shock and near the body. The implicit treatment of right hand side terms is also an important part of our method.
Keywords: Shock fitting; Smooth transformation of domain; Finite difference method; Implicit method.